Pengaruh Berbagai Level Kulit Pisang Fermentasi Terhadap Penampilan Itik Bali Jantan Umur 2-8 Minggu - I Wayan Wiarta; Ni Ketut Etty Suwitari; I Nyoman Kaca (Fakultas Pertanian, Universitas Warmadewa, 2019)
Balinese Duck is an Indonesian native duck that has been grown and maintained by Balinese society which is commonly maintained traditionally. Protein content of duck meat is quite high which is about 18.6-20.8. The main constraint faced in maintenance is the high cost of ration that reaches 60-70% of total production cost, the utilization of banana peel as animal feed besides reducing environmental pollution also can depress feed cost. After the fermentation of nutrient value of banana skin waste increased as crude protein from 6.56% to 14.88%, crude fiber from 15.32% to 11.43%. The design used in this study was a Completely Randomized Design consisted of 4 treatments (0, 7, 14, and 21% ducks fed with fermented banana peel flour). Each treatment consisted of 3 replications, so there were 12 plots of cages and each cage consisted of three Balinese Ducks at 2 weeks old. The number of male Balinese ducks used as many as 36 heads. The results of the statistical analysis gave no significant effect on the final body weight. The highest rate obtained at P1 1076.09 g tends to be higher than P3, P2, and P0. The weight gain in male Balinese ducks was statistically significant. The highest treatment was obtained at P1 689.09 g which tended to be higher than P3, P2, and P0. The amount of ration consumption during the study on the male Balinese ducks was statistically significant. The highest treatment was obtained at P1 that is 3671,15 g which tends to be higher than treatment of P2, P3, and P0. The addition of various levels of fermented banana peel flour statistically had an unreal effect on the highest treatment ration conversion obtained at P0 which was 5.43 followed by P2, P1, and P3 treatment. From the results of this research can be concluded that the provision of various levels of fermented banana peel did not give a real effect on the performance of Balinese Ducks from 2 to 8 weeks of age. Provision of various fermented banana peel levels at P1 (7%) tends to be higher than treatment P0, P2, and P3 against, final weight, weight gain, and consumption of Balinese Ducks ration of males aged 2-8 weeks.